Urinary incontinence: Prevalence and risk factors, association with anal incontinence and scope of incontinence in Turkish women - (:unkn) unknown (My University, 2004)
0

OBJECTIVE: To determine the prevalence and risk factors of urinary and anal incontinence and to assess women's response and point of view to urinary incontinence. STUDY DESIGN: The prevalence of overall, stress, urge, mixed urinary incontinence and anal incontinence was assessed by a multichoice questionnaire form in 1021 patients who admitted to outpatient gynecology clinics of our hospital. RESULTS: Of the 1021 patients, 162(15.9%) reported urinary incontinence, comprising 79(48.8%) with stress, 50(30.9%) with urge and 33(20.4%) with mixed urinary incontinence. There were significant differences regarding age, number of pregnancies and deliveries, route of delivery, duration of labor, infant birth weight, enuresis in childhood, enuresis nocturna, constipation, flatal and fecal incontinence between patients with and without urinary incontinence (p<0.05). In comparison of subgroups (stress, urge and mixed urinary incontinence) with patients without urinary incontinence, one by one, there were statistically significant differences concerning age, number of pregnancies and deliveries, route of delivery, and enuresis nocturna (p<0.05). Of the 1021 patients, 525(51.5%) reported flatal incontinence and 32(3.1%) reported fecal incontinence. The rates of flatal and fecal incontinence in patients with urinary incontinence were 65.4%(n=106) and 6.8%(n=11), respectively. Most of the women (66.1%) did not perceive urinary incontinence as a social or hygienic problem, however 84.6% of the patients with urinary incontinence did (p<0.0001). CONCLUSION: Ageing and obstetric events were the most prominent risk factors. According to our results, patients with urinary and anal incontinence could not yet seek for medical help. Education of population is important in order to avoid complications of incontinence.
Keywords: Kadın Hastalıkları ve Doğum